Utilization of Mycorrhizae and NPK Fertilizer in Nyawai (Ficus variegata Blume) Seedling Cultivation - NFN Danu; Rina Kurniaty; Y.M.M Anita Nugraheni (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2016)
Nyawai (Ficus variegata Blume) is a priority alternative tree species in the establishment of timber plantations. One of the factors determining the success of the development of nyawai forest plantations is the use of high quality seedlings because high quality seedlings would result high productivity stands. Application of fertilizer and mycorrhizal fungi can improve seedling quality. The purpose of this study is to get an optimum combination of fertilizer and mycorrhizal to produce high quality nyawai seedlings. Nyawai fruits were collected from Cibodas Botanical Garden Cianjur, Ir. H. Djuanda Grand Forest Park (Bandung), and Cikampek Forest Research. The experimental design used was randomized block design (RBD) with factorial pattern. Each replication consisted consisted of 30 seedlings Germination was done by sowing seed on the sprouting tubs contained by sterilized media. Transplanting media used sub soil plus mycorrhizal soil: without mycorrhizal (C0 ), Glomus sp. (C1 ), Acaulospora sp. (C2 ) and NPK : 0.0 g (P0 ), 0.5 g / polybag (P1 ), 1.0 g / poybag (P2 ). To produce nyawai seedling can use a mix media of subsoil + 30% coconut coir dust (coco peat) +10% rice husk (v / v), CMA Glomus sp and Acaulospora sp able to colonize with the roots of nyawai seedlings.